(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
We introduce an innovative and efficient methodology for improving the longevity and performance of dental implants while minimizing stress-shielding. By modifying the internal structure of the implant, two distinct strategies—topology optimization [1] and TPMS lattices—are employed to enhance implant design. These strategies are analyzed using an ANSYS model with material parameters from mechanical tests of additively manufactured Ti-6Al-4V. Topology optimized structures show a reduction in stress shielding compared to standard solid implants. Additionally, we presents a novel and efficient methodology based on the Hamilton principle [2,3] for modeling fatigue induced by damage and plasticity, focusing on speed and robustness. Traditional cycle-by-cycle simulations are inefficient for high-cycle fatigue due to excessive processing time. To overcome this, the proposed approach simulates the amplitude of the displacement load, bypassing the need for cycle-by-cycle analysis. This method allows for the simulation of force reactions over time within a changing time space, enabling the simple extraction of hysteresis loops and S-N curves during postprocessing without loss of accuracy. The long-term stability of the implants is further investigated using a high-cycle fatigue material model, revealing no fatigue in the selected topology optimized structures. Acknowledgments: DFG FOR5250, Project number: 449916462, TP-Z: Mechanism-based characterization and modeling of permanent and bioresorbable implants with tailored functionality based on innovative in vivo, in vitro and in silico methods. TP-7: In silico design of implants based on a multiscale approach References [1] Kick, M., Junker, P., Thermodynamic topology optimization for hardening materials, arXiv preprint arXiv:2103.03567, (2024). [2] Philipp Junker, Stephan Schwarz, Dustin R. Jantos, and Klaus Hackl. A fast and robust numerical treatment of a gradient enhanced model for brittle damage. International Journal for Multiscale Computational Engineering, 17(2):151–180, 2019. [3] Junker, P., Balzani, D. An extended Hamilton principle as unifying theory for coupled problems and dissipative microstructure evolution. Continuum Mech. Thermodyn. 33, 1931–1956 (2021). https://doi.org/10.1007/s00161-021-01017-z.